2007
DOI: 10.1118/1.2766758
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dosimetry for estimation of effective doses in multislice CT coronary angiography

Abstract: In vivo dosimetry represents a technique that has been widely employed to evaluate the dose to the patient mainly in radiotherapy. Considering the increment in dose to the population due to new high-dose multislice CT examinations, such as coronary angiography, it is becoming important to more accurately know the dose to the patient. The desire to know patient dose extends even to radiological examinations. Thermoluminescent dosimeters are considered the gold standard for in vivo dosimetry, but their use is ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The primary reason was that the relationship between the optical density of the film and dose is nonlinear in the relevant dose range. 18 In addition, our investigation indicated that narrower beam width was more sensitive to the film calibration (R 2 = 0.68 and 0.85 for FWHM and FWTM, respectively). It is worth noting that, in the subsequent routine measurement of FWHM and FWTM, all the scan parameters should be kept the same from year to year so as not to introduce unnecessary systemic variations.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The primary reason was that the relationship between the optical density of the film and dose is nonlinear in the relevant dose range. 18 In addition, our investigation indicated that narrower beam width was more sensitive to the film calibration (R 2 = 0.68 and 0.85 for FWHM and FWTM, respectively). It is worth noting that, in the subsequent routine measurement of FWHM and FWTM, all the scan parameters should be kept the same from year to year so as not to introduce unnecessary systemic variations.…”
Section: Discussionmentioning
confidence: 92%
“…23 Previous studies have recommended to conduct film calibration using single channel (usually red) only. 6,18 The reason was that the maximum absorption of Gafchromic films is typically seen at red wavelength. However, single channel dosimetry is very sensitive to background nonuniformity caused by film thickness variation and artifacts caused by document scanners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A calibration curve specific for the CT scanner beam quality was then obtained and it was used to convert the pixel values of the film into dose values (Figure 1). 7…”
Section: Methodsmentioning
confidence: 99%
“…The detailed analysis of ED in this study allowed the assessment of the relationship between dose length product (DLP) and ED 9,10,11,12,13 . The dose length product (DLP) was estimated using the volume computed tomography dose index (CTDI vol ) and the CT scan length 14 .…”
Section: Introductionmentioning
confidence: 99%